2004
DOI: 10.1111/j.1399-0004.2004.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Angelman syndrome: implications for autism research

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder characterized by severe mental retardation, ataxia, and a happy/sociable disposition. Maternally, but not paternally, derived defects, such as duplications, within the AS critical region result in autistic symptomatology, suggesting that the UBE3A gene might be implicated in the causation of autism. This study examined the prevalence of autism in AS in 19 children representing three known molecular classes of AS. Children were studied over the course of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(129 citation statements)
references
References 46 publications
2
124
0
2
Order By: Relevance
“…26 A recent study found that, among children with Angelman syndrome, those with comorbid autism scored lower on measures of language, adaptive behaviour, and cognition and demonstrated a slower rate of improvement over the course of the study. 27 Furthermore, deficits have been demonstrated in communication and socialization that mirror those observed in children with idiopathic autism.…”
Section: Prader-willi and Angelman Syndromesmentioning
confidence: 99%
“…26 A recent study found that, among children with Angelman syndrome, those with comorbid autism scored lower on measures of language, adaptive behaviour, and cognition and demonstrated a slower rate of improvement over the course of the study. 27 Furthermore, deficits have been demonstrated in communication and socialization that mirror those observed in children with idiopathic autism.…”
Section: Prader-willi and Angelman Syndromesmentioning
confidence: 99%
“…Patients with AS also often exhibit seizures, microcephaly, and autistic features (Peters et al, 2004). Partial seizures are the most frequent seizure type observed in patients with AS, followed by atonic seizures and atypical absences.…”
Section: Introductionmentioning
confidence: 99%
“…Angelman syndrome (AS) is a neurodevelopmental disorder characterized by intellectual disability, profound language impairment, seizures, and a propensity for a happy disposition (1)(2)(3). AS results from loss of function of the maternally inherited UBE3A allele at the 15q11-q13 locus (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%